Waktu Aplikasi Trichokompos dan Larutan Kelakai dalam Menentukan Kejadian Penyakit Layu Fusarium pada Tanaman Padi Beras Merah (Oryza nivara L.) - Nur Ain; Ismed Setya Budi; Mariana Mariana (www.ulm.ac.id, 2023)
Brown rice (Oryza nivara L.) is increasingly being cultivated along with the increasing needs of the community, such as health therapy using natural ingredients. One of the main diseases that attack brown rice is Fusarium wilt. Biological agents are an alternative control that is environmentally friendly and safe. The use of Trichocompost and Kelakai solution is an alternative that has the potential to control Fusarium wilt in brown rice plants. The aim of this study was to find out how long it took for the disease to appear in the red rice seedbeds after trichocompost and a solution of LALAI were applied. Six treatments and four replications were used in this study using a completely randomized design. The findings in this study indicated that trichocompost and lacteal solution prevented the development of Fusarium wilt in brown rice, the application time which suppressed disease development was application one week before planting and during transplanting. The application of trichocompost treatment and Lakalai solution was also proven to be able to extend the incubation period of the pathogen by 16.20 DAI when compared to plants without treatment at 9.80 DAI